The principal components of growth in the less developed countries - Headey, Derek D. (Wiley, 2008)
This paper re‐examines the international evidence on the sources of growth in less developed countries (LDCs) using exploratory factor analysis (EFA). Although EFA was first used in the development context by Adelman and Morris (1967) it has rarely been used since, despite being ideally suited to a context in which a large number of latent factors have been hypothesized to determine growth, and in which an even greater number of imperfectly measured and multicollinear proxies have been used to measure these latent factors. This paper uses EFA to minimize these problems of omitted variables biases, multicollinearity and measurement error, by reducing a large array of hypothesized growth determinants into a parsimonious and non‐collinear set of composite indices. The paper then provides theoretical interpretations of the derived indices, tests their statistical significance and quantitative importance in otherwise conventional growth regressions, and uses these results to reappraise the usefulness of cross‐country empirics in deriving robust, policy‐relevant knowledge of the principal components of growth in LDCs, including the so called ‘economic miracles’.